2019
DOI: 10.1136/heartjnl-2019-314763
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertase subtilisin/kexin 9 inhibitors in reducing cardiovascular outcomes: a systematic review and meta-analysis

Abstract: BackgroundTo evaluate the effects of proprotein convertase subtilisin/kexin 9 (PCSK9) inhibitors on major adverse cardiovascular events (MACE).MethodsOur systematic review included randomised controlled trials if they studied PCSK9 inhibitors in patients for primary and/or secondary prevention of cardiovascular diseases or with hypercholesterolaemia/hyperlipidaemia. Dichotomous variables from individual studies were pooled by relative risks (RR) and their 95% CIs using the random-effect model. Risk difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 69 publications
0
25
0
1
Order By: Relevance
“…Despite the effect of PCSK9 inhibitors on LDL-cholesterol, our review found that these drugs did not improve cardiovascular health. In contrast, previous meta-analyses have presented a statistically significantly reduced risk of major adverse cardiovascular events (MACE) [11,12,15,63]. MACE is a heterogeneously defined composite outcome that often includes interventions and may be susceptible to bias [64,65].…”
Section: Cardiovascular Outcomesmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite the effect of PCSK9 inhibitors on LDL-cholesterol, our review found that these drugs did not improve cardiovascular health. In contrast, previous meta-analyses have presented a statistically significantly reduced risk of major adverse cardiovascular events (MACE) [11,12,15,63]. MACE is a heterogeneously defined composite outcome that often includes interventions and may be susceptible to bias [64,65].…”
Section: Cardiovascular Outcomesmentioning
confidence: 97%
“…Second, prior systematic reviews about PCSK9 inhibitors included non-atherosclerotic types of myocardial infarction (MI) [10][11][12]. Besides spontaneous MI, clinical outcome trials have included MI due to supply-demand imbalance, cardiac death suggestive of MI without increased biomarkers, and MI related to revascularisation procedures [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…23 Ezetimibe and proprotein convertase subtilisin/kexin 9 (PCSK9) inhibitors are two new non-statin lipid-lowering drugs, which were suggested to reduce the cardiovascular events. 14,24 Compared to PCSK9 inhibitors, ezetimibe reduced only borderline risk of cardiovascular diseases (hazard ratio of ezetimibe, 0.936; 95% CI, 0.89 to 0.99 according to IMPROVE-IT trial vs relative risk of PCSK9 inhibitors, 0.84; 95% CI, 0.79 to 0.89 according to recent systematic review). 14,24 However, according to recent costeffectiveness analysis, PCSK9 inhibitors are too costly to be reasonably used in the US health system.…”
Section: Discussionmentioning
confidence: 99%
“…14,24 Compared to PCSK9 inhibitors, ezetimibe reduced only borderline risk of cardiovascular diseases (hazard ratio of ezetimibe, 0.936; 95% CI, 0.89 to 0.99 according to IMPROVE-IT trial vs relative risk of PCSK9 inhibitors, 0.84; 95% CI, 0.79 to 0.89 according to recent systematic review). 14,24 However, according to recent costeffectiveness analysis, PCSK9 inhibitors are too costly to be reasonably used in the US health system. 25 Although the prices of the two major PCSK9 inhibitors (alirocumab and evolocumab) were reduced consequently, they are still beyond the threshold of per capita GDP to be costeffective in most countries.…”
Section: Discussionmentioning
confidence: 99%
“…No differences between groups (PCSK9 inhibitors versus controls) were found for all-cause mortality, cardiovascular deaths, heart failure or unstable angina. 5 Interestingly, PCSK9 inhibitors and statins show similar effects on cardiovascular risk reduction per mg/dL reduction in LDL-C when the same duration of therapy is considered, that is, À14% (0-1 year of treatment), À17% (1-2 years of treatment) and À20% (2-3 years of treatment). 6…”
Section: Introductionmentioning
confidence: 99%